Prohibition of human trafficking in international law, a comparative study with national legislation (Journal of the College of Basic Education, 2023)
Human trafficking is a recognized violation of human rights and is prohibited by international law.It is a phenomenon that affects all countries and regions in the world. It is an organized crimeFrequently committed at the national and international levels it does not stop at any bordersgeographical, cultural, political or religious, as it is the third largest illegal trade inthe world after the illegal arms trade; And drug trafficking are the victims of thisCrime and its perpetrators alike hail from all parts of the world. protocol has been definedPreventing, suppressing and punishing trafficking in persons, especially women and children, supplementing the Convention of NationsUnited Nations Transnational Organized Crime Act 2000," Human Trafficking in ArticleThe third, paragraph (a), means “the recruitment, transportation, transfer, harboring, or reception of persons by means of:Threat or use of force or other forms of coercion, abduction, fraud, orDeception, abuse of power, abuse of a position of vulnerability, giving or receiving sums of money orAdvantages to obtain the consent of a person having control over another person for the purpose of exploitation, includingexploitation as a minimum; exploitation of the prostitution of others or other forms of sexual exploitation; or forced labouror forced service, slavery or practices similar to slavery, servitude or removalMembers"There is no doubt that there are many motives that cause the spread of the phenomenon of human trafficking, and the motivesIt is a group of factors that help stimulate the behavior or behavior of waterIt may have social, psychological or economic dimensions that push some towards this behavior